Ecology, Dharma and Direct Action: A Brief Survey of Contemporary Eco-Buddhist Activism in Korea - Yoon, Young-Hae; Jones, Sherwin (Buddhist Studies Review, 2015)
Over the last few decades there has emerged a small, yet influential eco-Buddhism movement in South Korea which, since the turn of the millennium, has seen several Son (J. Zen) Buddhist clerics engage in high-profile protests and activism campaigns opposing massive development projects which threatened widespread ecological destruction. This article will survey the issues and events surrounding three such protests; the 2003 samboilbae, or ‘threesteps- one-bow’, march led by Venerable Sukyong against the Saemangeum Reclamation Project, Venerable Jiyul’s Anti-Mt. Chonsong tunnel hunger-strike campaign between 2002 and 2006, and lastly Venerable Munsu’s self-immolation protesting the Four Rivers Project in 2010. This article will additionally analyze the attempts by these clerics to deploy innovative and distinctively Buddhist forms of protest, the effects of these protests, and how these protests have altered public perceptions of the role of Buddhist clergy in Korean society. This study will additionally highlight issues relevant to the broader discourse regarding the intersection of Buddhism and social activism, such as the appropriation of traditional Buddhist practices as protest tactics and the potential for conflict between social engagement and the pursuit of Buddhist soteriological goals.